2021
DOI: 10.1007/s00068-021-01784-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct discharge of patients with simple stable musculoskeletal injuries as an alternative to routine follow-up: a systematic review of the current literature

Abstract: Purpose There is growing evidence that patients with certain simple stable musculoskeletal injuries can be discharged directly from the Emergency Department (ED), without compromising patient outcome and experience. This study aims to review the literature on the effects of direct discharge (DD) of simple stable musculoskeletal injuries, regarding healthcare utilization, costs, patient outcome and experience. Methods A systematic review was performed in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(101 reference statements)
3
1
0
Order By: Relevance
“…Most health care professionals considered DD a safe alternative to face-to-face follow-up, leading to a perceived reduction of SHU. This finding is consistent with previous articles, which concluded that DD is safe based on low, comparable complication numbers, with significantly reduced SHU compared to traditional treatment [9,18,33]. The perceived reduction in SHU varied among stakeholders.…”
Section: Comparison With Existing Literaturesupporting
confidence: 90%
See 3 more Smart Citations
“…Most health care professionals considered DD a safe alternative to face-to-face follow-up, leading to a perceived reduction of SHU. This finding is consistent with previous articles, which concluded that DD is safe based on low, comparable complication numbers, with significantly reduced SHU compared to traditional treatment [9,18,33]. The perceived reduction in SHU varied among stakeholders.…”
Section: Comparison With Existing Literaturesupporting
confidence: 90%
“…Preliminary efficacy was partly in line with the literature [18,20,33]. Most health care professionals considered DD a safe alternative to face-to-face follow-up, leading to a perceived reduction of SHU.…”
Section: Comparison With Existing Literaturesupporting
confidence: 73%
See 2 more Smart Citations